Mapping microhabitat structure and connectivity on a tropical inselberg using UAV remote sensing. (June 2021) - Aristizábal-Botero, Ángela; Páez-Pérez, David; Realpe, Emilio; Vanschoenwinkel, Bram
In the past decade, unoccupied aerial vehicles (UAVs or drones) have emerged as powerful tools for ecologists, and the quality and diversity of information they can reconstruct is increasing. Rocky outcrops or inselbergs are complex three-dimensional (3D) ecosystems with several spatial microhabitats that are difficult to characterize using ground-based methods. UAV-mounted cameras and photogrammetric software can be used to obtain 3D models of whole inselbergs with a spatial resolution of up to 4cm and small areas with a spatial resolution of up to 8mm. The shape and volume of eroded depressions and channels can be reconstructed. This allows simulation of the flow of rainwater that creates local differences in hydrological conditions and connectivity among microhabitats. By capturing the near-infrared (NIR) light spectrum, we mapped proxies of photosynthetic activity. This revealed that the microphytic crusts of tropical inselbergs can have higher values of potential photosynthetic activity than the vegetation on the rock. Overall, we show that in systems where the major ecological gradients depend on the 3D structure of the landscape, drone imaging can help to reconstruct spatial variation in microhabitat structure, including proxies for habitat quality and connectivity.